מלאכת מחשבת: ברנהרט ליואל הופמן במבט מקרוב ומרחוק - אביצור דניאל (מכאן, 2010)
This essay is dedicated to interpreting Yoel Hoffman’s lyrical novel Bernhardt. It is arranged as “bottom-up” reading, proceeding from language through character and plot all the way to the context of Hoffman’s other works. In addition, this essay serves as a sort of “reader’s guide” to this supposedly “difficult” work, explicating literary allusions and exploring connections between the main plot, the fictions composed by the main character and the historical background. The results of this effort challenge prevalent opinions on Yoel Hoffman and Bernhardt. It is demonstrated that Bernhardt is not a collection of loosely related scenes, impressions and thoughts, but a cohesive novel, with significant character development, particular underlying values and relevant historical background.